Balancing Altered Calcium Metabolism with Bone Health in Sarcoidosis - Zhou, Ying; Lower, Elyse E. (Seminars in Respiratory and Critical Care Medicine, 2020)
Abnormal calcium metabolism in sarcoidosis patients can lead to hypercalcemia, hypercalciuria, and kidney stones. Hypercalcemia in sarcoidosis is usually due to increased activity of 1α-hydroxylase in macrophages of pulmonary granulomata, resulting in low levels of 25-hydroxyvitamin D and high levels of calcitriol. Vitamin D supplementation may be dangerous for some sarcoidosis patients and is recommended only for those with decreased 25-hydroxyvitamin D and reduced or normal calcitriol level. Diagnosis, treatment of osteoporosis, and maintenance of bone health are complex issues for sarcoidosis patients. An approach to diagnosis and treatment of bone fragility is presented.
Keywords: sarcoidosis; calcium metabolism; vitamin D; calcitriol; osteoporosis